Medical Ethics Education for Neurology Residents: Where Do We Go from Here? - Traner, Christopher B.; Tolchin, Dorothy W.; Tolchin, Benjamin (Seminars in Neurology, 2018)
Neurologists regularly confront complex clinical scenarios that require the application of ethical principles to achieve a respectful and fair resolution. In this article, we describe the types of ethically precarious scenarios neurologists encounter, the current status of standards for ethics and communication training for neurology residents, and the present practice of ethics training in neurology residency programs. We make recommendations for optimizing bioethics training for neurology residents and suggest methods for assessing the efficacy of these training initiatives. We emphasize the current need for strengthening the practical bioethics skills of neurologists.
Keywords: bioethics; medical education; communication education; neurology residency; postgraduate medical education